OPTIMIZING SOLAR OUTPUT TO REDUCE PHOTOVOLTAIC PANEL NUMBER IN IRRIGATION - Zeinaldeen, Laith. A. Zeinaldeen; Reeve, John. D. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This experiment aimed to study the effect of integrating a passive cooling system with varying air passage outlet clearances: 0 cm (C0, control), 10 cm (C1), 15 cm (C2), and 20 cm (C3) on the performance of polycrystalline and monocrystalline PV panels used in solar-powered irrigation systems. Performance metrics included PV efficiency, maximum power, required number of panels, and operational costs. Results showed a highly significant effect (P < 0.0001) of air passage clearance and PV type on all measured parameters. Specifically, the 10 cm clearance (C1) yielded the best outcomes, achieving the highest PV efficiency (16.26%), maximum power (41.12 W), lowest panel number (7), and lowest operational cost ($8.75). Among panel types, polycrystalline panels demonstrated superior efficiency (12.52%), maximum power (32.05 W), required fewer panels (11), and incurred lower operational costs ($13.50) compared to monocrystalline panels. These findings indicate that optimizing passive cooling can significantly enhance PV performance while reducing system size and costs.